THE DARK TRIAD – EMOTIONAL AND INTERPERSONAL CHARACTERISTICS - Tomić, Katarina N. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
The Dark triad is a construct of pathological personality traits, which consists of three components conceptually different, but still with significant empirical overlap: narcissism, Machiavellianism and subclinical psychopathy. The concept of Dark Triad found its place in the current structural models of personality, such as the Big-five and HEXACO model, and also an Interpersonal circumplex, within which the personal qualities project itselves into certain patterns of interpersonal behavior. This paper provides a brief theoretical overview of the basic elements of the Dark Triad, and an overview of current research related to (un) justified observation of the three constituent dimensions as a single construct in theoretical and empirical terms. Also, the paper presents an overview of the emotional dysfunctions typical for the triad, as well as the problems and consequences in the area of ​​interpersonal and social relations.